Phytoremediation of azo dye containing wastewater by using up-flow constructed wetlands - Danny Leonard Dugil (School of Environmental Engineering, University Malaysia Perlis, 2013)
This study assessed the treatment of azo dye Acid Orange 7 (AO7) a using three laboratory-scale up-flow constructed wetlands (UFCW) with and without supplementary aeration.